2019
DOI: 10.1111/hiv.12755
|View full text |Cite
|
Sign up to set email alerts
|

Planning HIV therapy to prevent future comorbidities: patient years for tenofovir alafenamide

Abstract: Since the introduction of suppressive antiretroviral therapy (ART), HIV has become a chronic disease, with infected people in high‐income countries approaching similar life expectancy to the general population. As this population ages, an increasing number of people with HIV are living with age‐, treatment‐, and disease‐related comorbidities. Lifestyle factors such as smoking, alcohol abuse, and substance misuse have a role in age‐related comorbidity. Some degree of immune dysfunction is suggested by the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…In addition, TAF received approval by the FDA for the treatment of HIV infection as a fixed dose combination with: cobicistat, elvitegravir and emtricitabine (Genvoya ® ) in November 2015 [22][23][24]; emtricitabine and rilpivirine hydrochloride (Odefsey ® ) in March 2016 [25]; emtricitabine (Descovy ® ) in April 2016 [26]; bictegravir sodium and emtricitabine (Biktarvy ® ) in February 2018; and cobicistat, darunavir and emtricitabine (Symtuza ® ) in July 2018 [27][28][29]. TAF exhibited an improved antiviral activity and safety profile related to renal and bone toxicity [30][31][32]. Therefore, TFV, TDF and in particular TAF represent key compounds for the treatment of chronic hepatitis B and HIV infections and are thus a subject of intense research in the area of new drug delivery systems [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TAF received approval by the FDA for the treatment of HIV infection as a fixed dose combination with: cobicistat, elvitegravir and emtricitabine (Genvoya ® ) in November 2015 [22][23][24]; emtricitabine and rilpivirine hydrochloride (Odefsey ® ) in March 2016 [25]; emtricitabine (Descovy ® ) in April 2016 [26]; bictegravir sodium and emtricitabine (Biktarvy ® ) in February 2018; and cobicistat, darunavir and emtricitabine (Symtuza ® ) in July 2018 [27][28][29]. TAF exhibited an improved antiviral activity and safety profile related to renal and bone toxicity [30][31][32]. Therefore, TFV, TDF and in particular TAF represent key compounds for the treatment of chronic hepatitis B and HIV infections and are thus a subject of intense research in the area of new drug delivery systems [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the osteoporosis foundation ( http://share.iofbonehealth.org/WOD/Compendium/2019-IOF-Compendium-of-Osteoporosis-PRESS.pdf ) the authors stress the strategies for preventing osteoporosis. The role of nutrition in maintaining bone health associated with a personalized anti-HIV treatment and daily vitamin supplementation to reduce early bone loss as well as a baseline DXA are critical steps for HIV Migrants and Refugees after arrival in the host countries [ 13 , 17 , 20 , 23 , 36 ]. High-risk groups should be first identified, and osteoporosis investigations should be carried out earlier than at 50 years of age [ 37 – 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Planning HIV therapy to prevent bone loss is crucial. We suggest the use of tenofovir alafenamide (TAF) molecule instead of tenofovir to reduce the risk of bone toxicity [35,36]. A recent study enrolled young HIV positive with low BMD showed tenofovir as a key molecule in ARV therapy [11].…”
Section: Plos Onementioning
confidence: 99%
“…Second, since many participants did not initiate HIV treatment at these two hospitals when the study was conducted, we could not find the association between bone loss and the individual antiretrovial agent and its exposure duration, such as TDF and PIs. Tenofovir alafenamide (TAF) and integrase inhibitors were recommended by most guidelines, and the future studies of TAF and integrase inhibitors in ageing HIV‐positive population are highly anticipated . Third, the sample size was relatively small, and there was no HIV‐negative comparator group.…”
Section: Discussionmentioning
confidence: 99%